2009
DOI: 10.1111/j.1745-4549.2009.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Storage Stability of Clarified Banana Juice Fortified With Inulin and Oligofructose

Abstract: Clarified banana juice fortified with inulin and oligofructose were stored for 8 weeks at 4, 25 and 35C. Changes in physicochemical characteristics (pH, total soluble solids [TSS], titratable acidity, sucrose, reducing sugars and turbidity), microbial count and sensory quality were determined. No differences were observed for pH and titratable acidity for all the stored juice samples. However, increase in turbidity was observed in all the juice samples, whereas juice samples stored at 35C recorded highest incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…The decrease in sucrose was attributed to the sucrose inversion into glocuse and fructose at higher temperature. Similar data was given by Yousaf et al (2009) for clarified banana juice fortified with inulin and oligofructose stored for 8 weeks at 4, 25 and 35°C. The sucrose content of samples stored at 4°C decreased due to the hydrolysis of sucrose, whereas samples stored at 25 and 35°C showed a slight increase in sucrose contents because of hydrolysis of inulin and oligofructose.…”
Section: Changes In Sugar Contentsupporting
confidence: 77%
See 1 more Smart Citation
“…The decrease in sucrose was attributed to the sucrose inversion into glocuse and fructose at higher temperature. Similar data was given by Yousaf et al (2009) for clarified banana juice fortified with inulin and oligofructose stored for 8 weeks at 4, 25 and 35°C. The sucrose content of samples stored at 4°C decreased due to the hydrolysis of sucrose, whereas samples stored at 25 and 35°C showed a slight increase in sucrose contents because of hydrolysis of inulin and oligofructose.…”
Section: Changes In Sugar Contentsupporting
confidence: 77%
“…The sucrose in juices might be hydrolyzed and converted to its monosaccharides (glucose and fructose) during storage. This conversion can be accelerated at high temperature (Yousaf et al 2009). Wang et al (2006) reported that after 150-day storage of carrot juice concentrate at 25 and 37°C, amount of sucrose was decreased while the glucose and fructose content was increased.…”
Section: Changes In Sugar Contentmentioning
confidence: 99%
“…Cerrutti et al (1997) evaluated the sensory properties of fruit purees containing different concentrations of vanillin and found that they had a pleasant vanillin flavor which maintained the typical taste of the fruit. Also, Yousaf, Yusof, Manap, Bin, and Abd-Aziz (2010) informed that clarified banana juice fortified with inulin and oligofructose remained acceptable during the 8 weeks of storage at 4 C and were rated the best for all the sensory parameters.…”
Section: Sensory Evaluation In Strawberry Juice Samplesmentioning
confidence: 99%
“…In addition, the loss of sucrose content was perhaps caused by microbes that utilised the sugars (Yusof et al, 2000). Several authors have shown that increases in the reducing sugar content and decreases in the sucrose content were observed in processed juice during storage such as apple juice concentrate (Babsky et al, 1986), banana juice (Yousaf et al, 2010) and sugar cane juice (Yusof et al, 2000;Singh et al, 2006). The increases in fructose and glucose and the decrease in sucrose were correlated with the invertase activity.…”
Section: Change In Invertase Activity Of Pasteurised Palmyra Palm Sapmentioning
confidence: 99%